Farmers' preferences for supermarket contracts in Kenya - Dennis O. Ochieng; Prakashan Chellattan Veettil; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2016)
With the modernization of global agri-food systems, the role of contract farming is increasing. This also involves smallholder farmers in developing countries. While previous studies have looked at economic impacts of contract schemes on smallholder farmers, little is known about farmers' preferences for contracting in general, and for specific contract design attributes in particular. Better understanding farmers' preferences and constraints is important to make smallholder contract schemes more viable and beneficial. This article builds on a choice experiment to analyze farmers' preferences and preference heterogeneity for contracts in Kenya. In the study region, supermarkets use contracts to source for fresh vegetables directly from preferred suppliers. However, farmer dropout rates are high. Mixed logit models are estimated to examine farmers' attitudes towards critical contract design attributes. Having to deliver their harvest to urban supermarkets is costly; hence farmers require a significant output price markup. Farmers also dislike delayed payments that are commonplace in contract schemes. The most problematic contract attribute is related to unpredictable product rejection rates, which substantially add to farmers' risk. Designing contracts with lower transaction costs, more transparent quality grading, and fairer risk-sharing clauses could enhance smallholder participation in supermarket procurement channels.
Keywords: O12; O13; Q12; Q13; Q18; 330; supermarkets; contracts; farmers' preferences; choice experiment; Kenya